Criminal Liability of Perpetrators who Intentionally and Unauthorized Alteration of Electronic Documents Based on the Electronic Information and Transactions Law (Study of Central Jakarta District Court Decision Number 724/Pid.Sus/2023/PN Jkt.Pst) - Beti Septiana Sari; Abunawas, Abunawas; Jamiatur Robekha (Jurnal Info Sains : Informatika dan Sains, 2025)
An electronic document is electronic information created, forwarded, sent, received, or stored in digital, electromagnetic, optical, or similar format, which can be viewed, displayed, and/or heard through a computer or electronic system. This document can be in the form of text, sound, images, or various other formats that convey meaning. The crime of altering electronic documents that causes harm to another person can be categorized as a cybercrime, particularly related to the manipulation of electronic information. The research method used is the normative juridical method, namely research that prioritizes library data, namely research on secondary data. The secondary data can be in the form of primary, secondary, or tertiary legal materials. Based on the research results, the author concludes that criminal liability for perpetrators of criminal acts intentionally and without authority to change electronic documents belonging to others that result in harm to others, can be enshrined by the Electronic Information and Transactions Law (UU ITE). The ITE Law regulates criminal sanctions for various actions related to electronic data manipulation. The relevant articles in the ITE Law related to illegal alteration of electronic documents include Article 27, Article 30, Article 32, Article 35, and Article 65. These articles regulate: a) Article 27: Prohibition on distributing, transmitting, and/or making accessible electronic information that contains content that violates morality, gambling, insults, or defamation; b) Article 30: Prohibition on unauthorized access to other people's computers or electronic systems; c) Article 35: Prohibition on falsifying electronic data; d) Article 65: Prohibition on using personal data that does not belong to them. Meanwhile, the sanctions, the perpetrator can be subject to criminal sanctions in the form of imprisonment and/or a fine, the amount of which varies depending on the article violated and the level of loss caused.